Freight Rates in Downside and Upside Markets: Pricing of Own and Spillover Risks from Other Shipping Segments - Savva, Christos S.; Theodossiou, Panayiotis; Tsouknidis, Dimitris (My University, 2019)
Shipping freight rates are notoriously volatile and shipping investors are perceived to be risk loving. The paper explores the stochastic properties of freight rates in the shipping industry and derives the analytical equations for their moments in downside and upside markets by using a two-piece extension of the generalized error distribution. Pricing equations developed across shipping segments show how conditional risk and conditional skewness are priced along with their risk spillover effects. Results reveal the existence of a positive skewness premium, suggesting that shipping investors are willing to accept lower expected returns for the opportunity to earn high pay-offs in the future.
Keywords: Stochastic properties; Freight rates